2009
DOI: 10.1111/j.1439-0272.1984.tb00234.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cooling, Freezing and Thawing Rates and Storage Conditions on Preservation of Human Spermatozoa

Abstract: Human spermatozoa was relatively resistant to cooling shock. However, when diluted semen was cooled faster than 10" C per minute from room temperature (RT) to 5" C and rewarmed to RT, percentage motility and percentage alive of spermatozoa decreased when compared to the slower cooling rates (< 5" Clmin). The optimum cooling rate from RT to 5" C resulting in maximum survival of human spermatozoa was found to be 0.5 to 1" C per minute when cooled from RT to 5" C and subsequently frozen-thawed inliquid nitroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2009
2009
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(19 citation statements)
references
References 16 publications
0
17
0
2
Order By: Relevance
“…It has been shown that the optimal initial cooling rate of the specimen from room temperature to 5°C is 0.5–1°C/min [10]. The sample is then frozen from 5°C to −80°C at a rate of 1–10°C/min.…”
Section: Techniques For Cryopreservationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the optimal initial cooling rate of the specimen from room temperature to 5°C is 0.5–1°C/min [10]. The sample is then frozen from 5°C to −80°C at a rate of 1–10°C/min.…”
Section: Techniques For Cryopreservationmentioning
confidence: 99%
“…Mitochondria are placed along the midpiece between the plasma membrane and the nine fibrous columns, to form a coating that provides energy necessary for sperm motility [27]. The greatest amount of energy is provided by molecules of ATP synthesized either by glycolysis in the cytoplasm [28] or through oxidative phosphorylation (oxphos) in the mitochondria [10]. …”
Section: Detrimental Effects Of Cryopreservation On Sperm Integritymentioning
confidence: 99%
“…Two factors which are important for successful freezing of semen are (1) slow cooling to + 5 O C (Mahadevan and Trounson -1984) and (2) adequate circulation of liquid nitrogen vapors around semen to produce uniform and fast rates of freezing from + 5 O C to -80 "C (Mahadevan and Trounson -1984;Hammitt and Martin -1988).…”
Section: Introductionmentioning
confidence: 99%
“…A second objective was to examine whether sperm survival following NCR freezing could be improved by thawing at a faster rate, in 40 O C water, than with thawing at the standard slower rate of room temperature (Mahadeven and Trounson -1984;Serafini and Marrs -1986). It was hypothesized that a faster rate of thawing might be required with NCR freezing because the rate of semen freezing from + 5 O C to -180°C was faster for the NCR than for the CR method.…”
Section: Introductionmentioning
confidence: 99%
“…la congélation et la décongélation (Mahadevan et Trounson 1984). Ces méthodes, basées sur un refroidissement lent dans le glycérol, ont été largement adoptées pour la conservation du sperme pour la FIV et l'IAD ).…”
Section: Ii42021 Historique Du Don De Spermeunclassified